Influences of ICP etching damages on the electronic properties of metal field plate 4H-SiC Schottky diodes*Project supported by the Suzhou Research Fund (No. BY2011129) and the State Grid Corporation of China Research Fund (No. 525500140003). (October 2015) - Wang 王, Hui 辉; Niu 钮, Yingxi 应喜; Yang 杨, Fei 霏; Cai 蔡, Yong 勇; Zhang 张, Zehong 泽洪; Zeng 曾, Zhongming 中明; Wang 王, Minrui 敏锐; Zeng 曾, Chunhong 春红; Zhang 张, Baoshun 宝顺
Abstract: Inductively coupled plasma (ICP) etching of 4H-SiC using SF6 /O2 gas mixture was studied systematically and the effect of etching was examined by metal field plate SiC Schottky diodes (SBDs). It was found that the etch rate as well as SiC surface morphology were related with ICP power, RF power, pressure, the flow of SF6 and O2 . Etching damages (the cone-in-pits and pits) generated at high chuck self-bias were observed, and they were thought to be caused by SiC defects. The degradation of both the reverse and forward I–V performances of SiC SBDs was ascribed to the cone-in-pits and pits. Moreover, the absolute value of forward current is even less than the reverse counterpart in the absolute value voltage range of 0–50 V for SiC SBDs with etching damages.